2021
DOI: 10.1111/jgs.17208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of music participation for mild cognitive impairment and dementia: A systematic review and meta‐analysis

Abstract: Objectives: To examine randomized controlled trials with active musicmaking interventions, in which older adults with probable mild cognitive impairment (MCI) or dementia physically participate in music, and their effects on cognitive functioning, emotional well-being, and social engagement.Participating in music-making is engaging and has shown diverse benefits. Additionally, this review categorized the music activities of each intervention.Design: Systematic review and meta-analysis. Setting: Long-term care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 47 publications
0
36
0
Order By: Relevance
“…As medications for AD only show limited benefits, musical interventions have become increasingly popular as a tool to sustain cognitive abilities as long as possible ( Leggieri et al, 2019 ). A recent systematic review and meta-analysis ( Dorris et al, 2021 ) could find a small but significant effect of musical training on cognitive functioning in elderly people with probable MCI or dementia. However, they did not discuss any brain correlates to these cognitive improvements.…”
Section: Discussionmentioning
confidence: 99%
“…As medications for AD only show limited benefits, musical interventions have become increasingly popular as a tool to sustain cognitive abilities as long as possible ( Leggieri et al, 2019 ). A recent systematic review and meta-analysis ( Dorris et al, 2021 ) could find a small but significant effect of musical training on cognitive functioning in elderly people with probable MCI or dementia. However, they did not discuss any brain correlates to these cognitive improvements.…”
Section: Discussionmentioning
confidence: 99%
“…Actively making music has been associated with enhanced intelligence [31,41,96] with neurocognitive and social gains for infants [22] as well as in elders [21,47,51,52]. High engagement in instrumental music activities throughout life could preserve and enhance neurocognition through advanced age [25]; gains can endure for 40 years [49].…”
Section: Discussionmentioning
confidence: 99%
“…Support for using interactive music intervention to enhance cognitive functioning in elders 65 and older with cognitive dysfunction was found in a review of studies that included 966 participants [51]. A review of recent studies with a total of 495 elders with "probable MCI or dementia" by clinical diagnosis, or whose MMSE scores were "between (and including) 13 and 26", also found improved cognitive functioning after "physically participating in" making music [21].…”
Section: Active Music Makingmentioning
confidence: 99%
“…Besides cognitive training, physical exercise is also popular as a recommendation among in people with MCI [17]. Music-making activities had a moderate effect on QOL compared to control conditions [18]. Social dancing is a combination of physical exercise and social activity; research on older Chinese women living in nursing homes showed that participating in Chinese square dancing groups resulted in higher QOL compared to being in a control group that maintained their usual lifestyle [19].…”
Section: Quality Of Life Inmentioning
confidence: 99%